IMPLEMENTASI SUPERVISI KEPALA SEKOLAH UNTUK PENINGKATAN KINERJA GURU DI SDN BABATAN 1/456 SURABAYA - Suntari, (Inspirasi Manajemen Pendidikan, 2016)
The headmaster’s supervision could help the improvement of teachers’ performance. The headmaster may havedirect supervision for teachers in order to know their difficulties, weaknesses, and needs during teaching and learning process. This research is purposed to describe the implementation of headmaster’s supervision to improve teachers’ performance at Elementary School 1/456 Babatan, Surabaya. The research used qualitative approach with case study plan. The way of the researcher to collect data was by interviewing, observing and documenting. The data analysis was by data reduction, data presentation, and data verification.After that, to know the validity of the data, the researcher used credibility, dependability, transferability, and conformability. The result of the research is: 1) the implementation of headmaster’s supervision at elementary school 1/456 babatan, surabaya has an important purpose which is to improve teachers’ performance. The headmaster’s supervision implements the two techniques, visiting the class and observing the class. It has flexible principle, friendly way and even professional. The headmaster’s supervision which used class visited technique is happened without the plan and teachers’ agreement because it is sudden action of the headmaster. Meanwhile, class observation technique is happened with a proper plan between teachers and headmaster to take the supervising activity. The implementation of headmaster’s supervision focused on teachers’ performance. Next, measuring and scoring the teachers’ performance is calculated by supervision instrument. 2) the teachers’ performance can be seen from the four competences such as teaching preparation, right media, teaching materials, and students’ task. The teaching preparation at elementary school 1/456 babatan, surabaya is by lesson plans while the media is facilitated based on the theme that would be taught to students. Teachers at elementary school 1/456 babatan, surabaya could master the materials by learning it first. Trough the lesson plans and the right media, teachers could master the materials well. Next, teachers at Elementary School 1/456 Babatan, Surabaya give students’ task in order to raise the students’ responsibility. Key words: headmaster’s supervision, teachers’ performance